DIÁLOGO ABERTO COM VERA MENEZES DE OLIVEIRA E PAIVA - Lima, Diógenes Cândido de (fólio - Revista de Letras, 2018)
Entrevistadores: Patrick Gomes Peixoto Danilo Pinheiro Lessa AlvesEnira Roberth Maia Lara Maria dos Santos Pires Jéssica Caroline Souza Aguiar Rodrigo B. de Sousa Danilo Sobral de Souza Pollyana Gomes Cardoso Jackson Souza Costa Leilian França dos Santos Patrícia Gomes Peixoto Lucas Maciel de Albuquerque